THE IMPORTANCE OF INDEPENDENT WORK IN THE MODERN EDUCATIONAL PROCESS (World Bulletin of Social Sciences, 2023)
In this article, the author highlights the importance of independent learning in the professional training of future teachers of musical culture, students' self-control skills in musical hearing in independent learning, the principles of organizing independent learning.